Modelling approach to nitrate adsorption on triamine-bearing activated rice husk ash - Phan, Phuoc Toan; Nguyen, Thai Anh; Nguyen, Nhat Huy; Nguyen, Trung Thanh (Engineering and Applied Science Research, 2020)
This work presents a systematic study of nitrate removal using amine grafted activated rice husk ash by batch adsorption. The effects of solution pH, adsorption time, amount of adsorbent, adsorption temperature, and initial nitrate concentration were investigated. Various adsorption models, such as Langmuir, Freundlich, Tempkin, Redlich-Peterson, and Dubinin-Radushkevich, were applied to determine the adsorption nature of this system. The most suitable model was found to be the Redlich-Peterson model for describing this adsorption process. Moreover, the adsorption process was endothermic and spontaneous, as shown by the obtained thermodynamic parameters. Finally, the competitive effect of inorganic anions was also evaluated and their effect was found to be in the descending order of PO43- > SO42- > HCO3- > Cl-.